Editorial - Honsawek, MD, Sittisak (Journal of Southeast Asian Orthopaedics, 2022)
In memoriam, it is with heartfelt sadness that we note the passing last year of Dr.Vinai Parkpian, MD, Emeritus Professor at Faculty of Medicine, Chulalongkorn University and King Chulalongkorn Memorial Hospital where he spent more than five decades of his medical career. Recognized as one of the nation’s foremost specialists in Orthopaedics, Dr. Vinai Parkpian served as the past president of the Thai Orthopaedic Association (TOA) and the Royal College of Orthopaedic Surgeons of Thailand (RCOST) and made extraordinary contributions to patient care, medical education, and orthopaedic research. He was a leading personality of Thai and international orthopaedic community, a great scientist, an impressive researcher, a prominent teacher, a fine surgeon, and a remarkable mentor to us all. Dr.Vinai Parkpian’s energy and enthusiasm for endless learning in science and medicine touched the lives of everyone who knew him. He will always remain in our hearts as an unforgettable teacher, a true friend and a perfect example of great surgeon and outstanding man. May our memories of him be a continuing source of inspiration. Over the past four years, it has been a great honour and an immense pleasure to serve as Associate Editor of The Thai Journal of Orthopaedic Surgery. It was a unique and exciting experience for me to contribute to our scientific community in this post and to interact with the many able people. As yet, we have had 40 volumes, which have included numerous published original articles, reviews, case reports, etc. Our journal has gone from strength to strength and I am pleased to state that we appear to have overcome our initial difficulties in so much that the journal now continues to prosper. As you are aware, we are successfully put The Thai Journal of Orthopaedic Surgery into the Thai Journal Citation Index (TCI), indicating that our journal has been indexed by TCI which is a citation database. As you will appreciate, all of this has taken a tremendous amount of time, contribution, and effort. I have to tell you that four years is a long time to be Associate Editor. As such, I think it is now appropriate that I pass on the torch to someone who can bring new ideas, energy, and perspectives to our journal. I also take the occasion of the close of my service to thank the members of the Editorial Board and peer reviewers of the journal for their faithful service and numerous reviews. I would like to express my sincere appreciation to Professor Thavat Prasartritha and Professor Sukit Saengnipanthkul, Associate Professor Pongsak Yuktanandana, and Professor Aree Tanavalee for providing me with the opportunity to work as Associate Editor. Especially, I would also like to extend my gratitude to those whose help and understanding made my time on The Thai Journal of Orthopaedic Surgery so enjoyable. My personal thanks go to all the authors who submitted manuscripts for consideration for publication, referees, members, and readers for their hard work, interest, and support for the journal over the years. Last but not least, I would like to thank our entire editorial office staff, particularly Jutamas Chearanaya and previously Supawinee Pattanasoon, who have worked tirelessly as the managing editor over all these years. Without this, the journal would undoubtedly not have been what it is today. Added to that, I am grateful to Aunchalee Juntee to handle the administrative details and contribute, in many ways, to the success of our publications; this is much appreciated.